Assessment of drivers and passengers seat belt compliances in Baghdad city - Abduljabbar, Ahmed Subhi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Baghdad city population is growing rapidly and soon it will reach 10 million, and this has increased the number of drivers on city streets which accompanied with the absence of adequate traffic enforcement and traffic control devices to match this increase. Current research main objective is to assess city drivers and passenger’s compliance to use seat belts as a safety precaution. The study consists of two main surveys conducted in the field considering gender, vehicle type, and other drivers characteristics. The first one consists of a questionnaire asking respondents to answer multiple choice questions about seat belt use and other questions associated with respondents’ demographics. Whereas second part involves observing seat belt use among city drivers and passengers at selected locations. Also, we sought information about seat belt use as a driver, front seat passenger, and rear seat passenger. Only 20% of the sample in field observational survey were wearing seat belt as a driver. Printed questionnaire reveals that only 12% are used to buckle up all the time, and 28% never use seat belt in their life, and the rest use seat belt occasionally. Seat belt rates for passengers were 5% only, and most passengers do not care about seat belts and many cars have disabled or malfunction seat belts. Four reasons for putting seat belt were considered and ranked as to avoid injuries, to avoid fines, to follow seat belt law, and wearing seat belt when people in the same car are wearing it.